2006
DOI: 10.1007/s10495-006-0528-4
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of cFLIP following reovirus infection sensitizes human ovarian cancer cells to TRAIL-induced apoptosis

Abstract: Tumor necrosis factor-related apoptosis inducing ligand (TRAIL) shows promise as a chemotherapeutic agent. However, many human cancer cells are resistant to killing by TRAIL. We have previously demonstrated that reovirus infection increases the susceptibility of human lung (H157) and breast (ZR75-1) cancer cell lines to TRAIL-induced apoptosis. We now show that reovirus also increases the susceptibility of human ovarian cancer cell lines (OVCAR3, PA-1 and SKOV-3) to TRAIL-induced apoptosis. Reovirus-induced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 64 publications
0
23
0
3
Order By: Relevance
“…Larochelle et al [1998] reported that Epstein-Barr virus-induced apoptosis may be mediated by FasL. Clarke and Tyler [2007] reported the reovirus-induced apoptosis via Tumor Necrosis Factor-related apoptosis-inducing ligand, and Kim et al [2007] reported that HIV could up-regulate the expression of Tumor Necrosis Factorrelated apoptosis-inducing ligand of antigen-presenting cell and induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Larochelle et al [1998] reported that Epstein-Barr virus-induced apoptosis may be mediated by FasL. Clarke and Tyler [2007] reported the reovirus-induced apoptosis via Tumor Necrosis Factor-related apoptosis-inducing ligand, and Kim et al [2007] reported that HIV could up-regulate the expression of Tumor Necrosis Factorrelated apoptosis-inducing ligand of antigen-presenting cell and induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Reoviruses are oncolytic viruses that multiply preferentially in tumor cells that harbor activated ras family or ras-signaling pathways, while sparing normal cells [127]. Recently, Clarke et al [128] demonstrated that reovirus infection results in the downregulation of c-FLIP and increased TRAIL-induced apoptosis in ovarian cancer cells, and overexpression of c-FLIP blocked reovirus-induced sensitization of these cells to TRAIL-induced apoptosis. Using oncolytic viruses aimed at downregulating c-FLIP may be potentially useful in combination with TRAIL and/or chemotherapeutic agents to eradicate cancer cells.…”
Section: Agents Known To Downregulate C-flipmentioning
confidence: 99%
“…Expression and modulation of expression has been examined in multiple tumour cell lines, including cell lines derived from carcinomas of the ovary, prostate, breast, urinary bladder and kidney [29][30][31][32][33][34]. In vivo, expression of these important caspase-8-inhibiting proteins has been shown in urothelial carcinomas, endometrial carcinomas and in Hodgkin lymphomas [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%